Pengaruh GCG, CSR, dan Intellectual Capital Terhadap Nilai Perusahaan dengan Investment Opportunity Set Sebagai Variabel Moderasi: (Studi Empiris Pada Perusahaan Teknologi Dan Telekomunikasi Yang Terdaftar Di BEI Tahun 2021-2023) - Valentry, Febiola; Zuliansyah, A; Hanief Musthofa, Ujang (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2025)
This study aims to determine and analyze whether good corporate governance, corporate social responsibility, and intellectual capital affect firm value with investment opportunity set as a moderating variable. This type of research is quantitative research, using secondary data. The data analysis method used is panel data regression test. The population in this study are technology and telecommunications companies listed on the IDX in 2021-2023. The data collection technique in this study was purposive sampling method with the results of 65 research populations into 11 companies with 3 years of observation, so that as many as 33 data were processed in this study. The results showed that good corporate governance has a significant positive effect on firm value. Corporate social responsibility has a significant negative effect on firm value. Intellectual capital doesn’t affect firm value. Investment opportunity set is not able to moderate the effect of good corporate governance, corporate social responsibility and intellectual capital on firm value.